High prevalence of plasmid-mediated Fosfomycin resistance in waterfowl-derived Escherichia coli strains: insights into genetic context and transmission dynamics in China - Zhang, Shaqiu; Yang, Jing; Yang, Qian; Li, Qianlong; Zhong, Zhijun; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Wu, Ying; et al. (Frontiers in Veterinary Science, 2025)
Fosfomycin (FOS) is a critical antibiotic for treating multi-drug resistant (MDR) Enterobacteriaceae infections, but its effectiveness is jeopardized by the dissemination of plasmids encoding enzymes that modify FOS. Despite the prohibition on its use in animal breeding in China, 100 strains of Escherichia coli (E. coli) exhibiting high resistance to FOS (MIC≥512 mg/L) were isolated from samples of waterfowl origin collected in Hainan, Sichuan, and Anhui. These strains commonly carried the fosA3 (88/100, 88.0%). In addition, 21 other antimicrobial resistance genes (ARGs) were detected in these strains, with high positivity rates for tetA, aphA1, sul2, folR, qnrS, and blaCTX-M. It is noteworthy that there was a significant positive correlation between the fosA3 and blaCTX-M (OR = 15.162, 95% CI: 1.875–122.635). The results of pulsed-field gel electrophoresis (PFGE) demonstrated the existence of multiple dispersed clonal clusters. Multilocus sequence typing (MLST) analysis identified 45 ST types, with ST48 and ST10 representing the most dominant clones. In the conjugation experiments, 53 fosA-like genes positive transconjugants were obtained with measurable conjugation frequency, which strongly demonstrated that these fosA3 may mainly locate on different types of plasmids possessing an efficient transmission ability. Whole genome sequencing (WGS) analysis further showed that the fosA3 was co-localized with the blaCTX-M on plasmids that showed a high degree of similarity in genetic structure. Of particular interest is the observation that the fosA3 is frequently accompanied by IS26 on either side of the gene. This structure may play a pivotal role in the horizontal transfer of the fosA3. The study revealed the alarming prevalence of FOS resistance in E. coli of waterfowl origin and delved deeply into the genetic characteristics and transmission mechanisms of the fosA3. The discovery of plasmid-mediated, transmissible FOS resistance in waterfowl E. coli poses a threat to “One Health”. There’s an urgent need for thorough monitoring and control measures against FOS resistance.